ANALYSIS OF LOCAL GOVERNMENT RESPONSES TOWARD MINING LAW NO 4 OF 2009 TO IMPROVE INVESTMENT CLIMATE IN TANAH BUMBU REGENCY IN 2014 - Febrianti Tentyana S (IPEM 15 UMY 490, 2015)
*490 The background of this research is basically related to Indonesia’s natural resources and its management. Indonesia is a big country with large amount of natural resources. Noted in 2010, Indonesia territorial area covers around 7.788.810.32 km2, within land area 1.910.931.32 km2, and population of 241.133.70 thousand people. The area is covering thousand islands also contains of various flora and fauna. Moreover, mineral resources is spread in five biggest islands; Borneo, Sumatera, Sulawesi, Papua, and Java. It is not surprisingly that Indonesia keep increase the number of mining production. Mining activity then becomes dilemma because of the negative impact of it especially for environment. The first two regulations is Mining Law No 1 of 1967 and No 11 of 1967 which was not based on mining object optimization. The latest regulation is Mining Law No 4 of 2009 which only started to be implemented in January 12nd 2014. However there are some points of this regulation cause harm for mining company, mainly for metal and iron mining company. The points are; first, smelter obligation for metal and iron ore mining company, due to upgrading the excavated object before export it; second, government ban the export of any mineral object before upgrading; and third, the system of contract has been changed to Mining License (Izin Usaha Pertambangan) which is valid for only five years. The direct impact of those points of regulation is the cessation of mineral mining sector which cause the decreasing of devises and local revenue. Meanwhile social impact of those points is layoffs for local worker. This research aimed to analyse the response of local government as the implementer of Mining Law No 4 of 2009 due to improve the investment climate. Since January 12nd 2014, there are at least two iron ore mining companies in Tanah Bumbu Regency have been cessed because of Mining Law No 4 of 2009 implemented. Based on the research, has been founded that local government could not be able to response this law implementation because of the other law. The latest Decentralization Law No 23 of 2014 was started since October 2014 by assigned the local government authority to provincial level. Since that time, local government has given deadline until October 2016 to hand up all mining documents to provincial level. Regarding to this law implementation, restructuring in local institution (Distamben) also needed because several mining inspectors are assigned to provincial level. Meanwhile, based on the research, local government of Tanah Bumbu Regency do not have sufficient strategy to attract the investor. It is because of the demographic issue in Tanah Bumbu Regency which is inaccessible for technology. Besides, local government have not provided sufficient facilities and infrastructure. That also became a reason of metal mining companies do not able to build a smelter. However, external factor also affecting the mining industry. Global economy since the late 2014 was decreasing affect the demand level of coal and other metal object. Moreover, mining product of Indonesia could not be able to match global demand